2002
DOI: 10.1073/pnas.052546099
|View full text |Cite
|
Sign up to set email alerts
|

Structure of spinach chloroplast F 1 -ATPase complexed with the phytopathogenic inhibitor tentoxin

Abstract: Tentoxin, a natural cyclic tetrapeptide produced by phytopathogenic fungi from the Alternaria species affects the catalytic function of the chloroplast F1-ATPase in certain sensitive species of plants. In this study, we show that the uncompetitive inhibitor tentoxin binds to the ␣␤-interface of the chloroplast F1-ATPase in a cleft localized at ␤Asp-83. Most of the binding site is located on the noncatalytic ␣-subunit. The crystal structure of the tentoxininhibited CF1-complex suggests that the inhibitor is hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…In the crystal structure of the CF 1 -tentoxin complex, a tentoxin molecule is bound at the high-affinity binding site located in a cleft at an ␣␤ subunit interface. Here, it blocks the contact between ␣Arg-297 and ␤Asp-83 (153,155), restrains the movements of these residues, and also restrains conformational changes at the catalytic interface. This may arrest the catalytic ␣␤ interface in the closed conformation and thereby hinder its transformation into the open conformation (153,155 (316,351) (Fig.…”
Section: Tentoxin and Its Derivativesmentioning
confidence: 99%
“…In the crystal structure of the CF 1 -tentoxin complex, a tentoxin molecule is bound at the high-affinity binding site located in a cleft at an ␣␤ subunit interface. Here, it blocks the contact between ␣Arg-297 and ␤Asp-83 (153,155), restrains the movements of these residues, and also restrains conformational changes at the catalytic interface. This may arrest the catalytic ␣␤ interface in the closed conformation and thereby hinder its transformation into the open conformation (153,155 (316,351) (Fig.…”
Section: Tentoxin and Its Derivativesmentioning
confidence: 99%
“…The most abundant protein complexes, such as PSII and PSI, cytochrome b 6 f, and ATP synthase, are photosynthetic apparatuses located at the thylakoid membrane for biogenesis. Intensive research into the photosynthetic protein complexes resolved the crystal structures of PSII/I, cytochrome b 6 f, and ATP synthase (Jordan et al, 2001;Zouni et al, 2001;Groth, 2002;Stroebel et al, 2003;Loll et al, 2005;Amunts et al, 2007;Umena et al, 2011). Combined with biochemical and functional analyses, structural studies have provided the detailed orientation of the cofactors and the molecular mechanism for photosynthesis.…”
mentioning
confidence: 99%
“…This means that a single tentoxin molecule bound to one binding site acts like a clamp as shown in Fig. 4A and inhibits the transition of the related ␤ subunit from a closed to an open conformation as suggested by the crystal structure of the spinach chloroplast F 1 complexed with tentoxin (11). This particular feature could be useful to mark a native enzyme at one position within a complete 360°turn.…”
Section: Molecular Processes Of Inhibition and Stimulationmentioning
confidence: 96%
“…The tentoxin-binding site is located at the contact surface between an ␣ and a ␤ subunit close to the N-terminal ␤-barrel structure on the ␣ 3 ␤ 3 hexagon. The crystal structure of spinach chloroplast F 1 complexed with tentoxin showed that the catalytic site on the ␣␤ pair with bound toxin is in a closed conformation (11). Thus, it was deduced that tentoxin inhibits the activity of the enzyme by blocking the conformational shifts at the catalytic sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation